New species and new records of Chloropinae from Singapore (Diptera: Chloropidae) - Riccardi, Paula Raile; Ang, Yuchen (Zootaxa, 2024)
Chloropidae biodiversity in the Oriental region is remarkably diverse and yet poorly understood. In this study, we used integrative taxonomy to tackle the species diversity of the subfamily Chloropinae from Singapore. We describe the first Oriental species of Cryptonevra Lioy, C. argenteum Riccardi, sp. nov., a new species of Chloropsina Becker, C. flavipes Riccardi, sp. nov., provide the first record of Eutropha noctilux (Walker) from Singapore and DNA barcodes of Chloropsina minima (Becker), Ensiferella kanmiyai Nartshuk. In addition, we increased the number of Chloropinae records from Singapore from two (Anthracophagella Anderson and Chlorops Meigen) to nine (addition of Cerais van der Wulp, Chloropsina, Cryptonevra, Elliponeura Loew, Ensiferella Andersson, Eutropha Loew, and Thressa Walker) genera and from two to seven described species plus four morphospecies. The species were discovered using NGS barcodes and are part of an ongoing campaign to document the biodiversity of Singapore.